The Behavior of Conventional and Islamic Bank Deposit Returns in Malaysia and Turkey - Charap, Joshua; Cevik, Serhan (Washington, D.C. : International Monetary Fund, 2011)
This paper examines the empirical behavior of conventional bank deposit rates and the rate of return on retail Islamic profit-and-loss sharing (PLS) investment accounts in Malaysia and Turkey, using monthly data from January 1997 to August 2010. The analysis shows that conventional bank deposit rates and PLS returns exhibit long-run cointegration and the time-varying volatility of conventional bank deposit rates and PLS returns is correlated and is statistically significant. The pairwise and multivariate causality tests show that conventional bank deposit rates Granger cause returns on PLS accounts. These findings have policy implications in terms of price stability and financial stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet